Influences of surface coatings and components of FePt nanoparticles on the suppression of glioma cell proliferation - Sun H (Dove Medical Press, 2012)
Haiming Sun,1,* Xiaohui Chen,2,* Dan Chen,1 Mingyan Dong,1 Xinning Fu,1 Qian Li,1 Xi Liu,1 Qingzhi Wu,1 Tong Qiu,1 Tao Wan,1 Shipu Li11State Key Laboratory of Advanced Technology for Materials Synthesis and Processing and Biomedical Materials and Engineering Center, Wuhan University of Technology, Wuhan, China; 2Department of Prosthetics, School of Stomatology, Wuhan University, Wuhan, China*Both authors contributed equally to this workAbstract: Malignant gliomas are primary brain tumors with high rates of morbidity and mortality; they are the fourth most common cause of cancer death. Novel diagnostic and therapeutic techniques based on nanomaterials provide promising options in the treatment of malignant gliomas. In order to evaluate the potential of FePt nanoparticles (NPs) for malignant glioma therapy, FePt NPs with different surface coatings and components were tunably synthesized using oleic acid/oleylamine (OA/OA) and cysteines (Cys) as the capping agents, respectively. The samples were characterized using X-ray diffraction, transmission electron microscopy (TEM), X-ray photon spectroscopy, Fourier transform infrared spectroscopy, atomic absorption spectrum, and zeta potential. The influence of the surface coatings and components of the FePt NPs on the proliferation of glioma cells was assessed through MTT assay and TEM observation using three typical glioma cell lines (glioma U251 cells, astrocytoma U87 cells, and neuroglioma H4 cells) as in vitro models. The results showed that the proliferation of glioma cells was significantly suppressed by lipophilic FePt-OA/OA NPs in a time- and/or dose-dependent manner, while no or low cytotoxic effects were detected in the case of hydrophilic FePt-Cys NPs. The IC50 value of FePt-OA/OA NPs on the three glioma cell lines was approximately 5–10 µg mL-1 after 24 hours’ incubation. Although the cellular uptake of FePt NPs was confirmed regardless of the surface coatings and components of the FePt NPs, the suppression of FePt NPs on glioma cell proliferation was dominantly determined by their surface coatings rather than their components. Therefore, these results demonstrate that, through engineering of the surface coating, FePt NPs can potentially be developed as novel therapeutic agents for malignant gliomas.Keywords: FePt nanoparticles, surface coatings, compositions, glioma cells, proliferation